A review of commodity murabahah transaction as offered by Bursa Malaysia: a critical analysis from fiqh perspective - Mohd Noor, Azman; Mahadi, Nur Farhah (2010)
Commodity Murābahah is an example of product innovation in Islamic banking and finance, which is based on Murābahah and Tawarruq transactions. Both traditional and the contemporary Islamic jurists hold different opinions on its legality in the light of Fiqh. This study is aimed at understanding of Commodity Murābahah trading especially the current practical operations and describing preferred structures of Commodities Murābahah as offered by Bursa Malaysia to overcome the highlighted controversies of Sharī'ah issues. This paper will illustrate in detail the transactional flow of Bursa Sūq Al-Sila' as operated by Bursa Malaysia and will shed light on related Sharīah issues for improvement.